2022
DOI: 10.3389/fphy.2022.816384
|View full text |Cite
|
Sign up to set email alerts
|

Cherenkov Radiation–Based Coincidence Time Resolution Measurements in BGO Scintillators

Abstract: Bismuth germanate oxide (BGO) scintillators can be re-introduced in time-of-flight positron emission tomography (TOF-PET) by exploiting the Cherenkov luminescence emitted as a result from 511 keV interactions. Accessing the timing information from the relatively few emitted Cherenkov photons is now possible due to the recent improvements in enhanced near-ultraviolet high-density (NUV-HD) silicon photomultiplier (SiPM) technology, fast and low noise readout electronics, and the development of efficient data pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…However, here, the variety of timing resolutions obtained from the different combinations of detected events is much wider than in cases investigated previously [27], [43]. Efthimiou et al [27], [43], studying Cherenkov-based detectors [44]- [48], reported that the complexity of the reconstruction with multiple (25) kernels slowed down their convergence. In this work, with only three Gaussian kernels, the Contrast Recovery Coefficient (CRC) converged slightly faster than the single and slower TOF kernel used for the BGO.…”
Section: Discussionmentioning
confidence: 67%
“…However, here, the variety of timing resolutions obtained from the different combinations of detected events is much wider than in cases investigated previously [27], [43]. Efthimiou et al [27], [43], studying Cherenkov-based detectors [44]- [48], reported that the complexity of the reconstruction with multiple (25) kernels slowed down their convergence. In this work, with only three Gaussian kernels, the Contrast Recovery Coefficient (CRC) converged slightly faster than the single and slower TOF kernel used for the BGO.…”
Section: Discussionmentioning
confidence: 67%
“…Although most modern PET systems are built using lutetiumbased scintillation crystals (e.g., lutetium-yttrium oxyorthosilicate [LYSO]) because of their high light yield and excellent timing properties, there has been a recent resurgence of studies that explore BGO, especially its achievable timing properties using prompt luminescence emissions (10). As the field is moving toward scanners with a long axial field of view, BGO is especially attractive because of its significantly decreased production cost and increased Z eff compared with lutetium-based crystals.…”
Section: Indirect Detection Methods (Scintillation Detection)mentioning
confidence: 99%
“…BGO crystals with dimensions of 2 × 2 × 3 mm also yielded a remarkable CTR value of 158 ± 3 ps. In other investigations with 3 × 3 × 3 mm BGO crystals [ 179 , 183 , 184 ], the capacitance compensated high-frequency SiPM readout electronics for measuring fast Cherenkov photons achieved timing resolution of 105–200 ps.…”
Section: Other Technologies To Improve Readout Performancementioning
confidence: 99%
“…Recent efforts to detect fast prompt photons, such as Cherenkov photons, have pushed the limits of timing performance in SiPM-based TOF PET detectors [178,179,[182][183][184][185][186]. When estimating the interaction time of gamma rays based on the prompt photons, the following two points should be considered [184]: (1) SiPM and subsequent readout electronics 19 Bootstrapping methods for SiPM capacitance compensation: a passive method using a balun transformer and b active method using a bootstrapping amplifier should have a single-photon timing resolution that is as low as possible and a − 3 dB bandwidth with > 1 GHz sampling rate [178,187], respectively; (2) Low noise level should be sufficiently low to avoid false triggers caused by the threshold equivalent to a few photon level [188].…”
Section: Cherenkov Photon Readoutmentioning
confidence: 99%
See 1 more Smart Citation